The use of digital tools in teaching general mathematics among senior high students - Aljas, Christine Joy D; Suana, Emma O; Saldivar, John Mark N (International Journal of Educational Technology and Learning, 2025)
This quasi-experimental study sought to find out the difference on the level of academic performance of students who used online learning modules in General Mathematics for the second quarter during school year 2021-2022 with self-learning modules provided by DepEd. This study used a control group with 30 randomly selected students and experimental group with another 30 students that were purposively selected. The online learning modules utilized digital and online tools such as Kahoot, Seesaw, personalized tutorial videos uploaded in YouTube, Quizziz applications, which were used to improve online assessments, as well as PowerPoint presentations used as supplement materials. Quantitative data were collected through post-tests, which were analyzed in concordance with the qualitative data from the focus group discussion. The findings found that the students' academic performance in General Mathematics in the experimental group was satisfactory while the control group did not meet expectations. Furthermore, there is also a huge disparity in the academic performance between those who chose modular distance learning and those students who opted online distance learning. It can be concluded that the use of digital tools in teaching General Mathematics is effective. Hence, the use of online learning modules in teaching General Mathematics is recommended as it promotes better student learning.